BRAND AWARENESS REBRANDING MUSEUM NASIONAL SEJARAH ALAM INDONESIA (MUNASAIN) - Diana Amaliasari; Qoute Nuraini Cahyaningrum; Dhea Riska Purwanty (UNIVERSITAS PAKUAN, 2022)
The purpose of this research was to aim regarding how the Public Relations of the Museum Nasional Sejarah Alam Indonesia (MUNASAIN) carried out rebranding and to find out which step of brand awareness carried out by the public relations of the MUNASAIN. The research method used in this research is descriptive qualitative. The results showed that the public relations of the MUNASAIN published information on rebranding, mostly through social media or online media, organized various special events or events, news was created by public relations and disseminated through the official MUNASAIN website and social media, disseminated information on the latest name change. through social relations with the community, besides that, public relations also attracts public attention by freeing entry fees as well as disseminating information about the change in the name of the museum. The MUNASAIN Public Relations’s also collaborates with the Ministry of Education and Culture and the Bogor City Tourism Office by disseminating information about the rebranding of the museum in joint activities, there are also activities in the form of social activities named Charity Day with the surrounding community and to form the concern of museum awareness along with efforts to build brand awareness of the museum to the public. The strategy implemented by public relations still places MUNASAIN at the lowest level of brand awareness, Unaware of Brand.